2019
DOI: 10.22159/ajpcr.2019.v12i1.27402
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analgesic and Anti-Inflammatory Activities of Purified Anthocyanin From Osbeckia Aspera (L.) Blume and Osbeckia Reticulata Bedd. Using Animal Models

Abstract: Objective: The objective of the present work is to isolate, purify, and fractionate anthocyanin from selected Osbeckia species and also to compare the analgesic and anti-inflammatory potentiality using animal models.Methods: Methodologies include extraction of anthocyanin from the in vitro callus culture of Osbeckia aspera and Osbeckia reticulata, purification using amberlite column chromatography, and fractionation by liquid chromatography-tandem mass spectrometry. The analgesic activity was determined by tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…23 Other research by Lawarence & Murugan (2019), showed slightly different results where the decrease in edema volume in the positive control group and the treatment group began at the 3 rd hour observation. 24…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…23 Other research by Lawarence & Murugan (2019), showed slightly different results where the decrease in edema volume in the positive control group and the treatment group began at the 3 rd hour observation. 24…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Moreover, we used micronucleus assay to assess genetic damage of aripiprazole in human peripheral blood lymphocytes. The development of the cytokinesis-block (CB) technique has transformed the humanlymphocyte micronucleus (MN) assay into a reliable and precise method for assessing chromosome damage (10,11) . On the other hand, cisplatin based combination chemotherapies have been used since the 1980's.…”
Section: Cytotoxic Effects Of Aripiprazole On Mkn45 and Nih3t3 Cell Lmentioning
confidence: 99%